Basophil activation through ASGM1 stimulation triggers PAF release and anaphylaxis‐like shock in mice. Issue 8 (27th May 2014) - Yang, Yan; Li, Daling; Katirai, Foad; Zhang, Bin; Xu, Yong; Xiong, Ping; Gong, Feili; Zheng, Fang
<x xml:space="preserve">Abstract</x> Basophils have been shown to contribute to anaphylaxis through either an IgE–FcεRI‐dependent pathway or an IgG–FcγR pathway. However, it remains largely unclear whether basophils can be activated to promote anaphylaxis via a non‐FcR pathway as well. The glycolipid receptor ASGM1 (Asialoganglioside gangliotetraosylceramide), which has an exposed GalNAcβ1–4Gal moiety and serves as a receptor for pathogen associated molecular patterns such as flagellin, was recently found to be expressed on basophils. Here, we demonstrate that stimulation of basophils with anti‐ASGM1 antibodies promotes platelet‐activating factor (PAF) secretion in vitro and in vivo. Moreover, we found that ASGM1 stimulation triggers basophil‐ and PAF‐dependent anaphylactic shock in pertussis toxin (PTX)‐pretreated mice. Thus, ASGM1 has a crucial role in basophil activation and basophil‐mediated anaphylaxis‐like shock in mice, especially when the vascular permeability is increased by PTX treatment. Our findings describe a novel anaphylaxis‐associated pathway that is antigen‐, antibody‐, and FcR‐independent.